Studi Kritis atas Metode Tafsir Tematis al-Qurâan - Kaltsum, Lilik Ummi (Program Pascasarjana UIN Sunan Ampel Surabaya, 2011)
This article is about a critical study of the thematic method of the Qurâan. It studies the nature of the method and provides a critical assessment of it. One of the gaps that the study will try to fill in is the lack of attention being given to the context out of which any particular text was revealed. The thematic approach is not particularly good at looking at the backgrounds of the text. It is this shortcoming that the paper will try to evaluate critically. It argues that the task of any interpreter of a text has been to understand first and foremost the surroundings that shape the text and constitute part and parcel of it. This understanding would determine the nature of the text and help guide the interpreter in the process of interpretation. The meaning of a text can change according to its context. The same word can infer to a different subject also according to the context. The paper will further elaborate this point further so as to give a clear idea that a thematic approach cannot ignore this aspect of exegesis.